Band Gap Tuning of Solution-Processed Ferroelectric Perovskite BiFe1-x Co x O3 Thin Films - Machado, Pamela (Chemistry of materials : a publication of the American Chemical Society, 2019)
Ferroelectric perovskite oxides are emerging as a promising photoactive layer for photovoltaic applications because of their very high stability and their alternative ferroelectricity-related mechanism for solar energy conversion that could lead to extraordinarily high efficiencies. One of the biggest challenges so far is to reduce their band gap toward the visible region while simultaneously retaining ferroelectricity. To address these two issues, herein an elemental composition engineering of BiFeO3 is performed by substituting Fe by Co cations, as a means to tune the characteristics of the transition metal-oxygen bond. We demonstrate by solution processing the formation of epitaxial, pure phase, and stable BiFe1-x Co x O3 thin films for x ≤ 0.3 and film thickness up to 100 nm. Importantly, the band gap can be tuned from 2.7 to 2.3 eV upon cobalt substitution while simultaneously enhancing ferroelectricity. As a proof of concept, nonoptimized vertical devices have been fabricated and, reassuringly, the electrical photoresponse in the visible region of the Co-substituted phase is improved with respect to the unsubstituted oxide